Upaya Peningkatan Pengetahuan tentang Penyakit Jantung Koroner pada Lansia di Posyandu Lansia Kelurahan Rawasari - Marta Suri (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2021)
Coronary heart disease is caused by various factors that can cause an increase in the incidence / deposits of cholesterol which narrow the vessels in the whole body including the coronary vessels. Coronary heart disease has become the leading cause of death in Indonesia. According to WHO in 2005, the number of deaths from cardiovascular disease (especially coronary heart disease, stroke, and rheumatic heart disease) increased globally to 17.5 million from 14.4 million in 1990. The results of the situation have been obtained from RT 12 KelurahanRawasariKecamatanAlamBarajo, Jambi City, in this sub-districthealth services such as Intregated Service Post (Posyandu) have been established. However, there is no scheduled health education as a promotive and preventive effort to overcome the problem of the high incidence of people experiencing heart disease. The results of health education activities for the elderly are expected to understand the concept of nursing problems that cause coronary heart disease